Benefits of Key Performance Indicators (KPI) and Proposed Applications in the Defense Industry: A Literature Review - Dipura, Santana; Soediantono, Dwi (IJOSMAS, 2022)
The purpose of this article is to explore the benefits of Key Performance Indicators (KPI) in various industries and provide recommendations to be applied to the defense industry. The method of writing this article is a literature review, which is a review by collecting, understanding, analyzing and then concluding as many as 21 international journal articles published from 2015 to 2021 regarding the application of Key Performance Indicators (KPI) in various industrial sectors and the defense industry. The analysis used used 21 content analysis of journal articles, then coding was carried out on the contents of the reviewed journals. The data that had been collected was then searched for similarities and differences and then discussed to draw conclusions. The results of the literature review analysis state that the application of Key Performance Indicators (KPI) can. Based on the results of the literature review, it can be concluded that the benefits of key performance indicators are that KPI makes it easier to determine items as translating from the financial and non-financial KPIs. The KPI chosen must be in accordance with the final goal of the proposed strategy which is a target determined by top management. With the impact of Covid-19, companies can use KPI as a decision-making tool during this pandemic as a strategy for employee reduction plans, expansion strategies (long-term relocation), strategies to reduce costs, and others. Determining a target, top management performs a projection or forecast that is adjusted to the available resources to describe the capacity of the process capability by comparing the benefits to be achieved by the company. Other factors are also compared between the achievements of the previous year as an illustration of determining a target. So that the target given will be in accordance with the SMART rules. Based on the literature review, it is recommended that key performance indicators be applied to the defense industry. . Based on the literature review, it is recommended that Key Performance Indicators (KPI) be applied to the defense industry.